Sorghum market segments: What are farmers’ needs for seed products in Tanzania? - Mbugua, M.; Donovan, J.; Rutsaert, P.; Gandhi, H.; Nas, T.M.; Templer, N.; de Sousa, K.; Mawia, Harriet; Ojiewo, C.; Gichuru, L.; Mwenda, E. (2024)
This brief explores Tanzanian farmers’ requirements for sorghum seed products as input for discussions by CGIAR and NARES on seed product market segmentation and the design of target product profiles (TPPs). We applied a novel approach to identify the requirements—video-based product concept testing (VPCT). Through multiple engagements with breeders, farmers, and industry, we identified seven sorghum seed-product concepts, five targeting the end use—home use, feed and food, industrial malting, food and fodder, forage; one concept on cropping system—intercropping; and one targeting material type—hybrid. We sampled 1,100 farmers from the Dodoma and Shinyanga Regions, where each farmer evaluated and ranked three concepts. Farmers were most likely to have selected the hybrid concept as their most preferred concept, followed by the home use concept. The results support discussions on refinements to sorghum segmentation. The hybrid segment should be prioritized, while the following new segments should be considered: home use, intercropping, food and fodder, food and feed. The forage segment should be maintained as a future market segment.